Channeling the past : politicizing history in postwar America - Christiansen, Erik, 1974- (Studies in American thought and culture., 2013)
"After the turmoil of the Great Depression and World War II, Americans looked to the nation's more distant past for lessons to inform its uncertain future. By applying recent and emerging techniques in mass communication--including radio and television programs and commercial book clubs--American elites working in media, commerce, and government used history to confer authority on their respective messages. With insight and wit, Erik Christiansen uncovers in Channeling the Past the ways that powerful corporations rewrote history to strengthen the postwar corporate state, while progressives, communists, and other leftists vied to make their own versions of the past more popular. Christiansen looks closely at several notable initiatives--CBS's flashback You Are There program; the Smithsonian Museum of American History, constructed in the late 1950s; the Cavalcade of America program sponsored by the Du Pont Company; the History Book Club; and the Freedom Train, a museum on rails that traveled the country from 1947 to 1949 exhibiting historic documents and flags, including original copies of the U.S. Constitution and the Magna Carta. It is often said that history is written by the victors, but Christiansen offers a more nuanced perspective: history is constantly remade to suit the objectives of those with the resources to do it. He provides dramatic evidence of sophisticated calculations that influenced both public opinion and historical memory, and shows that Americans' relationships with the past changed as a result"--Publisher's description.